Oral Manifestations of Gastrointestinal Diseases - Tom D Daley; Jerrold E Armstrong (Canadian Journal of Gastroenterology)
The present paper offers a detailed review of the oral manifestations of various gastrointestional diseases or conditions, with suggestions on how they may be relevant to the practice of gastroenterology. The review includes Crohn’s disease, ulcerative colitis, Gardner syndrome, Peutz-Jeghers syndrome, malabsorption conditions related to hematopoiesis, gastrointestinal malignancy metastatic to the jaws, jaundice and gastric reflux diseases.